Haematological Characteristics, Body Metabolites, Electrolytes And Enzymes As Predictors Of Physical Fitness Variable Explosive Leg Strength Among Hockey Players (Journal of Pharmaceutical Negative Results, 2023)
This study aimed to investigate the predictive capacity of haematological characteristics, body metabolites, electrolytes and enzymes on physical fitness variable explosive leg strength among sub-junior male hockey players in Himachal Pradesh. Twenty players aged 14-16 years, who had participated in Sub-Junior National Level Championships during 2022-2024, were assessed. The study employed a non-experimental, correlational research design to analyze the relationships and predictive strength of 25 physiological markers with the physical fitness component explosive leg strength. The data was collected using SAI Physical Fitness Tests and laboratory blood analyses. Pearson correlation and regression analyses were conducted. The findings revealed that red blood cells (RBCs) and haemoglobin exhibited a significant positive relationship with explosive leg strength, while white blood cells (WBCs) showed a non-significant negative association. Among body metabolites, no significant correlations were found. Potassium demonstrated a significant negative relationship among electrolytes, contributing meaningfully to the regression model. None of the enzymes studied significantly correlated with explosive leg strength. The regression models confirmed that haematological traits and electrolytes, particularly RBCs and potassium, were significant predictors of explosive leg strength, accounting for 60.5% and 67.5% variance respectively. These insights emphasize the role of internal physiological factors, especially blood and electrolyte markers, in determining physical fitness characteristics important for athletic performance in hockey.